Even More Excellent Html With Xml, Xhtml, and Javascript - T.Gottleber Timothy (McGraw -Hill, 2003)
HTML texts from other academic publishers treat HTML in a step-by-step cookbook fashion, as though it were a simple software application, limiting the amount of material and concepts covered. Unique in the marketplace, Gottleber and Trainor’s Even More Excellent HTML combines the pedagogical support of academic texts with the comprehensive coverage found in trade books. No previous knowledge of HTML or Web design is assumed. --This text refers to the Paperback edition.